Behind the teacher change: Learning a ton while there are dilemmas - Nur Arifah Drajati; Agustina Tyarakanita; Sri Haryati; Dewi Rochsantiningsih (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
This study investigates teachers’ dilemmas when encountering changes in teaching and learning after participating in an online community of practice (OCoP). As teachers have a vital role and should have crucial skills in creating conducive practice and facilitating the learners’ engagement and motivation in learning. Changes in teaching practices, such as the implementation of new strategies, are important because they can improve the quality of learning. However, these changes often challenge teachers, especially when balancing curriculum demands, student needs, and resource constraints. Moreover, teachers also bump into several dilemmas when implementing new practices learned from the online community of practice (OCoP). Within narrative case study, the data set of the study contains Zoom meeting observation and WhatsApp transcript between mentors and teachers and primary data of narrative stories gained from the three English teachers’ spoken interview. Moreover, teachers show that their dilemmas were associated with four parties: school, teacher, student, and the policymaker. Their contradicting belief and practices between existing and new practices are not for addressing potential dilemmas of an obstacle but as a direction to the new practice. This study revealed that teachers changed their beliefs and teaching practices significantly. These changes included shifting from transmission patterns to a combination of transmission and heuristics and an increased use of English. Teachers overcame these dilemmas by employing reflective strategies and innovative practices acquired through OCoP. It confirms that OCoP plays an important role in helping teachers manage dilemmas and develop professional practices. Active participation in OCoP is an effective strategy for dealing with changes in the teaching profession.